2012
DOI: 10.1007/s11434-012-5400-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of partial 14-3-3 genes in the marine sponge Hymeniacidon perleve and its role in differentiating infectious and non-infectious bacteria

Abstract: Sponges (phylum Porifera) are the phylogenetically oldest metazoa and highly efficient filter feeders. In the marine ecosystem, they are unconditionally exposed to environmental stresses. Understanding the sponge-bacteria interaction is hence of both ecological and biological significance. This study investigated the specific interaction between the sponge Hymeniacidon perleve and the non-infectious bacteria, Escherichia coli and infectious bacteria, Vibrio spp. by measuring the 14-3-3 mRNA expression of H. pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, other than the use of antimicrobial compounds, sponges possess efficient defense mechanisms that recognize pathogens and initiate an immune response. Sponges distinguish between infectious and non-infectious bacteria through molecular responses, receptor molecules and membrane proteins [ 115 117 ]. Bacteria associated with sponges are able to produce molecules which act on the sponge cells by inhibiting its immune and apoptotic system [ 118 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other than the use of antimicrobial compounds, sponges possess efficient defense mechanisms that recognize pathogens and initiate an immune response. Sponges distinguish between infectious and non-infectious bacteria through molecular responses, receptor molecules and membrane proteins [ 115 117 ]. Bacteria associated with sponges are able to produce molecules which act on the sponge cells by inhibiting its immune and apoptotic system [ 118 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sponges can succumb to bacterial infection where their cells become overrun with bacteria causing death to the organism [36]. Fu et al [37] demonstrated the infection of the marine sponge Hymeniacidon perleve with Vibrio spp. through genetic markers for cell death.…”
Section: Discussionmentioning
confidence: 99%